Laparoscopic repair of a late-presenting Bochdalek diaphragmatic hernia with acute gastric volvulus. (20th March 2013) - Hadjittofi, Christopher; Matter, Ibrahim; Eyal, Ori; Slijper, Nadav
Abstract : An otherwise healthy 17-year-old boy presented to the paediatric emergency department with acute severe epigastric pain. An admission abdominal radiograph demonstrated gastric dilation, associated with an elevated left hemidiaphragm. Subsequent barium contrast imaging confirmed the diagnosis of organoaxial acute gastric volvulus (AGV). Emergent exploratory laparoscopy revealed AGV with migration of the stomach, spleen, pancreatic tail, splenic flexure, left kidney and adrenal through a left-sided Bochdalek diaphragmatic hernia. Following careful mobilisation of the displaced structures, a mesh closure of the diaphragmatic defect was performed. The patient's postoperative chest radiograph was unremarkable, and he was discharged on the sixth postoperative day after an uneventful recovery. At 2 months the patient was well and asymptomatic, with normal barium contrast imaging results.